2020
DOI: 10.3390/cancers12030646
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Antiviral Signalling and Carcinogenesis in Human Papillomavirus Infections

Abstract: Human papillomaviruses (HPV) are the causative agents of the most common sexually transmitted infection worldwide. While infection is generally asymptomatic and can be cleared by the host immune system, when persistence occurs, HPV can become a risk factor for malignant transformation. Progression to cancer is actually an unintended consequence of the complex HPV life cycle. Different antiviral defence mechanisms recognize HPV early in infection, leading to the activation of the innate immune response. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 142 publications
(250 reference statements)
0
37
0
4
Order By: Relevance
“…The combined oncogenic effects of viral infections have been recognized as potential oncogenic drivers in various cancers [ 6 ]. Oncoviruses can lead to the onset and progression of cancer via commonly shared pathways including WNT/β-catenin, JAK/STAT/SRC, PI3k/Akt/mTOR, and/or RAS/MEK/ERK signaling pathways [ 6 , 8 , 14 , 41 ]. A study conducted by Guidry and Scott [ 63 ] showed that co-infection by HPV and EBV enhances EBV persistence either via latency or increased viral replication or by aggregating HPV oncogene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined oncogenic effects of viral infections have been recognized as potential oncogenic drivers in various cancers [ 6 ]. Oncoviruses can lead to the onset and progression of cancer via commonly shared pathways including WNT/β-catenin, JAK/STAT/SRC, PI3k/Akt/mTOR, and/or RAS/MEK/ERK signaling pathways [ 6 , 8 , 14 , 41 ]. A study conducted by Guidry and Scott [ 63 ] showed that co-infection by HPV and EBV enhances EBV persistence either via latency or increased viral replication or by aggregating HPV oncogene expression.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is a small epitheliotropic, non-enveloped, double-stranded DNA virus that can be sexually transmitted. It infects the epidermal or mucosal epithelial cells, where HPVs can induce neoplastic transformation (both benign and malignant) [ 7 , 8 ]. The multiplication of the virus occurs in cell nuclei and is firmly linked to cell differentiation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human papillomavirus (HPV), a non-enveloped double-stranded DNA virus is transmitted sexually [ 6 , 7 ]. The HPV genome consists of eight open reading frames (ORFs) and is separated into three functional elements; the early (E) region which encodes six proteins (E1, E2, E4–E7) and is involved in regulating viral transcription and replication, the late region that encodes the structural proteins (L1 and L2) and is involved in viral assembly, and, the long control region [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, IFN responses are detrimental to persistent HPV infections, reducing cellular proliferation and causing apoptosis, episome loss, mutation, and/or integration [73][74][75][76][77]. Likewise, it is well known that some HPV early genes-E5, E6, and E7 -counteract these detrimental antiviral IFN and IFN-stimulated gene (ISG) responses through a variety of mechanisms [78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%